Composition, molded article, laminate and resin

By using fluororesin A and B with specific groups (I) in the composition, the affinity between fluororesin and resin B is improved, and the problem of poor appearance of wire material due to fluororesin aggregation is solved, and the effect of suppressing aggregation and maintaining a good appearance while increasing the fluororesin ratio is achieved.

CN119923445APending Publication Date: 2025-05-02YAMAGATA UNIVERSITY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380068676.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-28
Filing Date
2023-09-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

With increasing the fluororesin ratio, the affinity between the liquid crystal polymer and the fluororesin decreases, resulting in aggregation of the fluororesin and affecting the appearance of the thread material.

Method used

A composition is adopted, which comprises a fluororesin A having a specific group (I) and a resin B having a melt flow rate of 30 g/10 minutes or more at a melt point +12°C. By bonding the group (I) to the functional groups in the resin, the affinity between the fluororesin and the resin B is increased, and the aggregation of the fluororesin is inhibited.

Benefits of technology

The aggregation of fluororesin is effectively suppressed, and even when the proportion of fluororesin increases, the good appearance of the wire material can be maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923445A_ABST
    Figure CN119923445A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a composition, a molded body, a laminate, and a resin which are capable of suppressing aggregation of a fluororesin, which causes a poor appearance of a wire material, even when the proportion of the fluororesin increases. The present disclosure relates to a composition containing a fluororesin A and a resin B having a melt flow rate of 30 g / 10 minutes or more at a melting point + 12 DEG C (excluding the fluororesin A), at least one of the fluororesin A and the resin B having a group (I) represented by the following formula (in the formula, R1 and R2 are the same or different, are hydrogen or an organic group, and may bond to each other to form a cyclic structure. A double line represented by a solid line and a dashed line is a single bond or a double bond. ). # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a composition, a molded body, a laminate, and a resin. Background Art

[0002] Various studies have been conducted on compositions containing fluororesins and liquid crystal polymers (for example, refer to Patent Documents 1 to 3).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2001-187833

[0006] Patent Document 2: Japanese Patent Application Publication No. 2018-177931

[0007] Patent Document 3: Japanese Patent Application Publication No. 2019-065061 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The present inventors have conducted research and found that, as in the examples of Patent Documents 2 and 3, when the proportion of fluororesin is increased, the affinity between the liquid crystal polymer and the fluororesin decreases, and the fluororesin is easily aggregated (poor dispersion). Aggregation of the fluororesin leads to poor appearance of the strands, so it is preferable to prevent aggregation of the fluororesin as much as possible.

[0010] An object of the present disclosure is to provide a composition, a molded product, a laminate, and a resin capable of suppressing the aggregation of a fluororesin which causes a poor strand appearance even when the proportion of the fluororesin is increased.

[0011] Means for solving problems

[0012] The present disclosure (1) is a composition (hereinafter also referred to as "the composition of the present disclosure") comprising a fluororesin A and a resin B (excluding the above-mentioned fluororesin A) having a melt flow rate of 30 g / 10 minutes or more at a melting point of +12°C, wherein at least one of the above-mentioned fluororesin A and the above-mentioned resin B has a group (I) represented by the following formula.

[0013] [Chemistry 1]

[0014]

[0015] (Where R 1 and R 2 The same or different, are hydrogen or organic groups, are not bonded to each other or are bonded to form a ring structure, and the double lines represented by solid and dotted lines are single bonds or double bonds.)

[0016] The present disclosure (2) is the composition according to the present disclosure (1), wherein the thermal decomposition temperature of the fluororesin A and / or the resin B is 330° C. or higher.

[0017] The present disclosure (3) is the composition described in the present disclosure (1) or (2), wherein the fluororesin A is at least one selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers and tetrafluoroethylene / hexafluoropropylene copolymers.

[0018] The present disclosure (4) is the composition according to any one of the present disclosures (1) to (3), wherein the resin B is at least one selected from the group consisting of liquid crystal polymers, polyetherimides, polyphenylene sulfides, polyaryletherketones, polysulfones, and polyethersulfones.

[0019] The present disclosure (5) is the composition according to any one of the present disclosures (1) to (4), wherein the content of the fluororesin A is 10% by volume or more.

[0020] The present disclosure (6) is the composition according to any one of the present disclosures (1) to (5), wherein the group (I) is an oxazoline group.

[0021] The present disclosure (7) is the composition according to the present disclosure (6), wherein the oxazoline group is derived from an oxazoline compound.

[0022] The present disclosure (8) is a molded product (hereinafter also referred to as “a molded product of the present disclosure”) comprising the composition according to any one of the present disclosures (1) to (7).

[0023] The present disclosure (9) is the molded article described in the present disclosure (8), which is used for a dielectric material.

[0024] The present disclosure (10) is a laminate (hereinafter also referred to as "laminated body of the present disclosure") comprising a metal foil and the molded body described in the present disclosure (8) or (9).

[0025] The present disclosure (11) is the laminate according to the present disclosure (10), wherein the metal foil is copper.

[0026] The present disclosure (12) is a resin (hereinafter also referred to as "resin of the present disclosure") having a group (I) represented by the following formula and having a thermal decomposition temperature of 330°C or higher.

[0027] [Chemistry 2]

[0028]

[0029] (Where R 1 and R 2The same or different, are hydrogen or organic groups, are not bonded to each other or are bonded to form a ring structure, and the double lines represented by solid and dotted lines are single bonds or double bonds.)

[0030] The present disclosure (13) is the resin described in the present disclosure (12), wherein the resin contains an amide group and an ester group.

[0031] The present disclosure (14) is the resin according to the present disclosure (12) or (13), wherein the group (I) is an oxazoline group.

[0032] The present disclosure (15) is the resin according to the present disclosure (14), wherein the oxazoline group is derived from an oxazoline compound.

[0033] The present disclosure (16) is the resin according to any one of the present disclosures (12) to (15), wherein the melt flow rate at melting point + 12°C is 30 g / 10 min or more.

[0034] The present disclosure (17) is the resin of the present disclosure (16), which is a liquid crystal polymer, polyetherimide, polyphenylene sulfide, polyaryletherketone, polysulfone or polyethersulfone.

[0035] The present disclosure (18) is the resin according to any one of the present disclosures (12) to (15), which is a fluororesin.

[0036] The present disclosure (19) is the resin described in the present disclosure (18), wherein the fluororesin is at least one selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers and tetrafluoroethylene / hexafluoropropylene copolymers.

[0037] The present disclosure (20) is the resin described in the present disclosure (18) or (19), wherein the fluororesin is insoluble in an aprotic solvent.

[0038] The present disclosure (21) is the resin described in the present disclosure (20), wherein the above-mentioned aprotic solvent is at least one selected from the group consisting of perfluoroaromatic compounds, perfluorotrialkylamines, perfluoroalkanes, hydrofluorocarbons, perfluorocyclic ethers, hydrofluoroethers and olefin compounds containing at least one chlorine atom.

[0039] The present disclosure (22) is the resin according to any one of the present disclosures (12) to (21), which is a resin modifier.

[0040] Effects of the Invention

[0041] According to the present disclosure, it is possible to provide a composition, a molded product, a laminate, and a resin capable of suppressing the aggregation of the fluororesin which causes poor strand appearance even when the proportion of the fluororesin is increased. DETAILED DESCRIPTION

[0042] In the present specification, the "organic group" refers to a group containing one or more carbon atoms, or a group formed by removing one hydrogen atom from an organic compound.

[0043] Examples of the "organic group" include:

[0044] an alkyl group which may have one or more substituents,

[0045] an alkenyl group which may have one or more substituents,

[0046] an alkynyl group which may have one or more substituents,

[0047] a cycloalkyl group which may have one or more substituents,

[0048] a cycloalkenyl group which may have one or more substituents,

[0049] a cycloalkadienyl group which may have one or more substituents,

[0050] an aryl group which may have one or more substituents,

[0051] an aralkyl group which may have one or more substituents,

[0052] a non-aromatic heterocyclic group which may have one or more substituents,

[0053] a heteroaryl group which may have one or more substituents,

[0054] Cyano,

[0055] Formyl,

[0056] RaO-,

[0057] RaCO-,

[0058] RaSO2-,

[0059] RaCOO-

[0060] RaNRaCO-,

[0061] RaCONRa-

[0062] RaOCO-,

[0063] RaOSO2-, and

[0064] RaNRbSO2-

[0065] (In these formulas, Ra is independently

[0066] an alkyl group which may have one or more substituents,

[0067] an alkenyl group which may have one or more substituents,

[0068] an alkynyl group which may have one or more substituents,

[0069] a cycloalkyl group which may have one or more substituents,

[0070] a cycloalkenyl group which may have one or more substituents,

[0071] a cycloalkadienyl group which may have one or more substituents,

[0072] an aryl group which may have one or more substituents,

[0073] an aralkyl group which may have one or more substituents,

[0074] A non-aromatic heterocyclic group which may have one or more substituents, or

[0075] a heteroaryl group which may have one or more substituents,

[0076] Rb is independently H or an alkyl group which may have one or more substituents).

[0077] As the organic group, an alkyl group which may have one or more substituents is preferred.

[0078] Hereinafter, the present disclosure will be described in detail.

[0079] <Composition of the present disclosure>

[0080] The composition of the present disclosure comprises fluororesin A and resin B (excluding fluororesin A) having a melt flow rate (MFR) of 30 g / 10 min or more at melting point + 12° C., at least one of which has a group (I) represented by the following formula.

[0081] [Chemistry 3]

[0082]

[0083] (Where R 1 and R 2 The same or different, are hydrogen or organic groups, are not bonded to each other or are bonded to form a ring structure, and the double lines represented by solid and dotted lines are single bonds or double bonds.)

[0084] According to the composition of the present disclosure, since at least one of the fluororesin A and the resin B has the group (I), the affinity between the fluororesin A and the resin B can be improved. As a result, even when the proportion of the fluororesin is increased, the aggregation of the fluororesin which causes poor strand appearance can be suppressed.

[0085] This effect is presumed to be produced by bonding of the group (I) present in one resin with a functional group such as a carboxyl group, a phenolic OH group, a thiol group, etc. present in another resin. It is believed that the bonding mentioned here is not only a covalent bond but also a non-covalent interaction such as a hydrogen bond that also exerts an effect.

[0086] In the composition of the present disclosure, either or both of the fluororesin A and the resin B may have the group (I), and preferably at least the fluororesin A has the group (I).

[0087] The group (I) may be introduced into the terminal of the polymer constituting the fluororesin A or the resin B, may be introduced into the side chain, or may be introduced into both the terminal and the side chain. It is preferably introduced into at least the terminal.

[0088] The polymer constituting the fluororesin A and the resin B may have a branched structure. When the polymer has a branched structure, the main chain may have the group (I), the side chain may have the group (I), or both the main chain and the side chain may have the group (I). Preferably, at least the main chain has the group (I), and more preferably, the terminal of the main chain has the group (I).

[0089] R 1 and R 2 The organic group is as described above.

[0090] As R 1 and R 2 Examples of the ring structure formed by bonding include a cyclohexane ring and a benzene ring.

[0091] From the perspective of being able to react with carboxyl groups introduced into many resins to form stable amide ester bonds, R 1 and R 2 It is preferably hydrogen, and the double line represented by the solid line and the dotted line is preferably a single bond. That is, the group (I) is preferably an oxazoline group.

[0092] The oxazoline group is preferably derived from an oxazoline compound. That is, the oxazoline group introduced is preferably an oxazoline group in an oxazoline compound.

[0093] There is no particular limitation on the method of introducing group (I) into the resin. The compound having group (I) may be copolymerized during the polymerization of the resin, or the side chain, terminal, etc. may be modified (modified) with the compound having group (I) after the polymerization of the resin not having group (I). The compound having group (I) may also be grafted.

[0094] In addition, other compounds may be further reacted with the resin (polymer) having the group (I).

[0095] The compound having the group (I) such as the oxazoline compound may be a polymer, an oligomer, or a low molecular weight compound other than these.

[0096] The low molecular weight compound having the group (I) is preferably a compound containing a benzene ring or a naphthalene ring.

[0097] In the low molecular weight compound having group (I), the number of group (I) may be 1 or more, preferably 2 or more. The upper limit is not particularly limited. The position of group (I) may be appropriately set according to the number of groups (I) and the structure of the compound.

[0098] The structure of the polymer or oligomer having the group (I) is not particularly limited, and may or may not contain a benzene ring or a naphthalene ring.

[0099] In the polymer or oligomer having group (I), the number of group (I) may be 1 or more, preferably plural (2 or more). There is no particular upper limit on the number of groups (I). There is no particular limit on the position of group (I).

[0100] The weight average molecular weight (Mw) of the polymer having the group (I) is preferably 10,000 to 500,000, and the number average molecular weight (Mn) is preferably 5,000 to 200,000.

[0101] Mw and Mn can be determined from the PS-equivalent weight average molecular weight in GPC measurement.

[0102] Specific examples of the compound having group (I) include oxazoline compounds which are low molecular weight compounds, such as 2-vinyl-2-oxazoline, 4-methyl-2-vinyl-2-oxazoline, 5-methyl-2-vinyl-2-oxazoline, 4-ethyl-2-vinyl-2-oxazoline, 5-ethyl-2-vinyl-2-oxazoline, 4,4-dimethyl-2-vinyl-2-oxazoline, 4,4-diethyl-2-vinyl-2-oxazoline, 4,5-dimethyl-2-vinyl-2-oxazoline, 4,5-diethyl-2-vinyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 4-methyl-2-isopropenyl-2-oxazoline, 5-methyl-2-isopropenyl-2-oxazoline, Propylene-2-oxazoline, 4-ethyl-2-isopropenyl-2-oxazoline, 5-ethyl-2-isopropenyl-2-oxazoline, 4,4-dimethyl-2-isopropenyl-2-oxazoline, 4,4-diethyl-2-isopropenyl-2-oxazoline, 4,5-dimethyl-2-isopropenyl-2-oxazoline, 4,5-diethyl-2-isopropenyl-2-oxazoline, 1,3-phenylbisoxazoline [1,3-PBO], 1,4-phenylbisoxazoline [1,4-PBO], etc. Examples of the polymeric oxazoline compound include poly-2-vinyl-2-oxazoline [Pvozo] and Epocros (registered trademark) manufactured by Nippon Shokubai Co., Ltd. Among them, 1,3-PBO and Pvozo are preferred, and 1,3-PBO is more preferred.

[0103] Specific examples of the compound having the group (I) other than the oxazoline compound include 1,4-bis(benzoxazol-2-yl)naphthalene [1,4-BBN] and the like.

[0104] Examples of the fluororesin A include polytetrafluoroethylene [PTFE], tetrafluoroethylene [TFE] / perfluoro(alkyl vinyl ether) [PAVE] copolymers [PFA], TFE / hexafluoropropylene [HFP] copolymers [FEP], ethylene [Et] / TFE copolymers [ETFE], Et / TFE / HFP copolymers [EFEP], polychlorotrifluoroethylene [PCTFE], chlorotrifluoroethylene [CTFE] / TFE copolymers, CTFE / TFE / PAVE copolymers, and Et / CTFE copolymers.

[0105] As the fluororesin A, from the viewpoint of affinity with the resin B, at least one selected from the group consisting of polytetrafluoroethylene [PTFE], tetrafluoroethylene [TFE] / perfluoro(alkyl vinyl ether) [PAVE] copolymer [PFA] and tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP] is preferred, at least one selected from the group consisting of PFA and FEP is more preferred, and FEP is further preferred.

[0106] The PTFE may be a TFE homopolymer composed of only tetrafluoroethylene (TFE) units, or may be a modified PTFE containing TFE units and modified monomer units based on a modifying monomer copolymerizable with TFE.

[0107] The PTFE may be a TFE homopolymer composed of only tetrafluoroethylene (TFE) units, or may be a modified PTFE containing TFE units and modified monomer units based on a modifying monomer copolymerizable with TFE.

[0108] As the modifying monomer, there is no particular limitation as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP]; fluorochloroolefins such as trifluorochloroethylene [CTFE]; hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VdF]; perfluorovinyl ether; perfluoroalkyl allyl ether; (perfluoroalkyl)ethylene; ethylene, etc. In addition, the modifying monomer used may be one or more.

[0109] The perfluorovinyl ether is not particularly limited, and examples thereof include the following general formula (1):

[0110] CF2=CF-ORf (1)

[0111] (wherein Rf represents a perfluoro organic group) and the like. In the present specification, the above-mentioned "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced by fluorine atoms. The above-mentioned perfluoro organic group may have an ether oxygen.

[0112] Examples of perfluorovinyl ethers include perfluoro(alkyl vinyl ether) [PAVE] in which Rf in the general formula (1) represents a perfluoroalkyl group having 1 to 10 carbon atoms. The perfluoroalkyl group preferably has 1 to 5 carbon atoms.

[0113] Examples of the perfluoroalkyl group in PAVE include perfluoromethyl, perfluoroethyl, perfluoropropyl, perfluorobutyl, perfluoropentyl, and perfluorohexyl. Preferably, the perfluoroalkyl group is perfluoro(propyl vinyl ether) [PPVE] in which the perfluoroalkyl group is perfluoropropyl.

[0114] As the perfluorovinyl ether, further examples include those in which Rf in the general formula (1) is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and Rf is the following formula:

[0115] [Chemistry 4]

[0116]

[0117] (wherein m represents 0 or an integer of 1 to 4) and Rf is the following formula:

[0118] [Chemistry 5]

[0119]

[0120] (wherein n represents an integer of 1 to 4) and the like.

[0121] The (perfluoroalkyl)ethylene is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE], (perfluorohexyl)ethylene [PFHE], and (perfluorooctyl)ethylene.

[0122] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VdF, PPVE, PFBE and ethylene, and more preferably at least one selected from the group consisting of HFP and CTFE.

[0123] In modified PTFE, the content of the above-mentioned modified monomeric unit is preferably in the range of 0.00001 to 1.0 mass %. As the lower limit of the content of the modified monomeric unit, it is more preferably 0.0001 mass %, more preferably 0.001 mass %, and further preferably 0.005 mass %, especially more preferably 0.010 mass %, and particularly preferably 0.030 mass %. As the upper limit of the content of the modified monomeric unit, it is preferably 0.90 mass %, more preferably 0.50 mass %, further preferably 0.40 mass %, and further more preferably 0.30 mass %.

[0124] In this specification, the modified monomer unit refers to a part of the molecular structure of the modified PTFE and is derived from the modified monomer.

[0125] The melting point of PTFE is preferably 324 to 360° C. The melting point of PTFE is the first melting point. The first melting point is the temperature corresponding to the maximum value in the heat of fusion curve when PTFE that has not been heated to a temperature of 300° C. or higher is heated at a rate of 10° C. / min using a differential scanning calorimeter [DSC].

[0126] The standard specific gravity (SSG) of PTFE is preferably 2.130 to 2.280. The standard specific gravity is more preferably 2.220 or less, more preferably 2.200 or less. In addition, it is preferably 2.140 or more, more preferably 2.150 or more. The SSG is measured using a sample molded according to ASTM D 4895-89 and by a water displacement method according to ASTM D-792.

[0127] PTFE preferably has non-melt secondary processability. Non-melt secondary processability refers to the property that the melt flow rate cannot be measured at a temperature higher than the crystallization melting point according to ASTM D-1238 and D-2116.

[0128] PFA is not particularly limited, but preferably the molar ratio of TFE unit to PAVE unit (TFE unit / PAVE unit) is 70 / 30 or more and less than 99 / 1. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.9 / 1.1 or less. The above-mentioned PFA preferably contains 0.1 to 10 mol% of monomer units derived from monomers copolymerizable with TFE and PAVE (a copolymer in which the total of TFE unit and PAVE unit is 90 to 99.9 mol%), more preferably 0.1 to 5 mol%, and particularly preferably 0.2 to 4 mol%.

[0129] Examples of monomers copolymerizable with TFE and PAVE include HFP, formula (I): CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 are the same or different, representing a hydrogen atom or a fluorine atom, Z 4 represents a hydrogen atom, a fluorine atom or a chlorine atom, and n represents an integer of 2 to 10. ) and a vinyl monomer represented by formula (II): CF2=CF-OCH2-Rf 1 (Where Rf 1 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) represents an alkyl perfluorovinyl ether derivative, formula (X): CZ 5 Z 6 =CZ 7 -CZ 8 Z 9 -O-Rf 4 (In the formula, in the formula, Z 5 , Z 6 and Z 7 are the same or different, representing a hydrogen atom, a chlorine atom or a fluorine atom, Z 8 and Z 9 represents a hydrogen atom or a fluorine atom, Rf 4 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) and the like. As the allyl ether monomer, preferably, CH2=CFCF2-O-Rf 4 CF2=CFCF2-O-Rf 4 (perfluoroalkyl allyl ether), CF2=CFCH2-O-Rf 4 、CH2=CHCF2-O-Rf 4 (Where Rf 4 The same as in the above formula (X) etc.

[0130] Examples of monomers copolymerizable with TFE and PAVE include unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, and anhydrides of unsaturated dicarboxylic acids such as itaconic acid, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride.

[0131] The melting point of PFA is preferably 180 to less than 324°C, more preferably 230 to 320°C, and further preferably 280 to 320°C.

[0132] There are no particular restrictions on the FEP, but preferably the copolymer has a molar ratio of TFE unit to HFP unit (TFE unit / HFP unit) of 70 / 30 or more and less than 99 / 1. A more preferred molar ratio is 70 / 30 or more and 98.9 / 1.1 or less, and a further preferred molar ratio is 80 / 20 or more and 98.9 / 1.1 or less. The above-mentioned FEP preferably contains 0.1 to 10 mol% of monomer units derived from monomers copolymerizable with TFE and HFP (a copolymer having a total of 90 to 99.9 mol% of TFE unit and HFP unit), more preferably 0.1 to 5 mol%, and particularly preferably 0.2 to 4 mol%.

[0133] Examples of monomers copolymerizable with TFE and HFP include PAVE, monomers represented by formula (X), alkyl perfluorovinyl ether derivatives represented by formula (II), etc. Examples of monomers copolymerizable with TFE and HFP include unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, and anhydrides of unsaturated dicarboxylic acids such as itaconic acid, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride.

[0134] The melting point of FEP is preferably 150°C to less than 324°C, more preferably 200 to 320°C, and further preferably 240 to 320°C.

[0135] As ETFE, preferably the molar ratio of TFE unit to ethylene unit (TFE unit / ethylene unit) is 20 / 80 or more and 90 / 10 or less. A more preferred molar ratio is 37 / 63 or more and 85 / 15 or less, and a further preferred molar ratio is 38 / 62 or more and 80 / 20 or less. ETFE can be a copolymer consisting of TFE, ethylene and a monomer copolymerizable with TFE and ethylene. The monomer unit of the above-mentioned ETFE preferably comes from a monomer copolymerizable with TFE and ethylene, which is 0.1 to 10 mol% (a copolymer in which the TFE unit and the ethylene unit add up to 90 to 99.9 mol%), more preferably 0.1 to 5 mol%, and particularly preferably 0.2 to 4 mol%.

[0136] As monomers copolymerizable with TFE and ethylene, the following are mentioned:

[0137] CH2=CX1 R 2 CF2=CFRf 2 CF2=CFORf 2 、CH2=C(Rf 2 )2(where X 1 represents a hydrogen atom or a fluorine atom, Rf 2 represents a fluorinated alkyl group which may contain an ether bond. ) represented by a monomer, a monomer represented by formula (X), among which CF2=CFRf is preferred. 2 CF2=CFORf 2 and CH2=CX 1 R 2 The fluorine-containing vinyl monomer represented by formula (X), more preferably HFP, CF2=CF-ORf 3 (Where Rf 3 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) represents a perfluoro(alkyl vinyl ether), CF2=CF-CF2-O-Rf 4 (Where Rf 4 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) represents a perfluoroalkyl allyl ether and Rf 2 CH2=CX is a fluoroalkyl group having 1 to 8 carbon atoms 1 R 2 In addition, examples of monomers copolymerizable with TFE and ethylene include unsaturated monocarboxylic acids, unsaturated dicarboxylic acids, and anhydrides of unsaturated dicarboxylic acids such as itaconic acid, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic anhydride.

[0138] The melting point of ETFE is preferably 140°C to less than 324°C, more preferably 160 to 320°C, and further preferably 195 to 320°C.

[0139] The content of each monomer unit of the above polymer can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis according to the kind of monomer.

[0140] The thermal decomposition temperature of the fluororesin A is preferably 330°C or higher, more preferably 350°C or higher, further preferably 370°C or higher, and is preferably 500°C or lower, more preferably 480°C or lower, further preferably 470°C or lower.

[0141] It should be noted that the thermal decomposition temperature of fluororesin A was measured using a thermal analyzer STA7200 manufactured by Hitachi High-Tech Science. The measurement was performed under a nitrogen purge atmosphere of 200 mL / min. 10 mg of the sample was placed in an aluminum pan, kept at 25°C for 10 minutes, and then heated to 600°C at a heating rate of 10°C / min. The temperature (Td5) at which the initial mass was reduced by 5% was taken as the thermal decomposition temperature.

[0142] Fluororesin A per 10 6 The number of carbon atoms in the main chain can be 100 to 2000 unstable terminal groups. The unstable terminal groups are -COF and -COOH, and the above number is their total number.

[0143] It should be noted that the number of unstable terminal groups can be determined by infrared spectroscopy. Specifically, first, fluororesin A is melt-extruded to form a film with a thickness of 0.25 to 0.3 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain the infrared absorption spectrum of fluororesin A, and a differential spectrum with the background spectrum of a completely fluorinated material without the presence of unstable terminal groups is obtained. From the absorption peak of the specific unstable terminal group that appears in the differential spectrum, the number of unstable terminal groups per 10 in fluororesin A is calculated according to the following formula (A). 6 The number N of unstable terminal groups of a carbon source.

[0144] N=I×K / t(A)

[0145] I: Absorbance

[0146] K: Correction coefficient

[0147] t: film thickness (mm)

[0148] The composition of the present disclosure preferably forms a sea-island structure in which the resin B serves as the sea and the fluororesin A serves as the islands.

[0149] As resin B, there is no particular limitation as long as the melt flow rate (MFR) at melting point + 12°C is 30 g / 10 minutes or more, and liquid crystal polymers, polyetherimides, polyphenylene sulfides, polyaryletherketones, polysulfones, polyethersulfones, etc. can be used. Among them, at least one selected from the group consisting of liquid crystal polymers, polyetherimides, polyphenylene sulfides, polyaryletherketones, polysulfones, and polyethersulfones is preferred, at least one selected from the group consisting of liquid crystal polymers, polyetherimides, polyphenylene sulfides, polyetheretherketones, polysulfones, and polyethersulfones is preferred, and liquid crystal polymers are particularly preferred.

[0150] The liquid crystal polymer is not particularly limited, and may be a polymer having a liquid crystalization temperature (i.e., melting point) of 180° C. to 380° C., preferably a thermotropic liquid crystal polymer that becomes a liquid crystal state such as a nematic state by heating, for example, the following liquid crystal polymers are preferred:

[0151] Type I liquid crystal polymers (biphenol / benzoic acid / parahydroxybenzoic acid (POB) copolymers, etc.),

[0152] Type II liquid crystal polymers (hydroxynaphthoic acid (HNA) / POB copolymers, etc.),

[0153] Type III liquid crystal polymer (POB / ethylene terephthalate copolymer, etc.).

[0154] Among them, from the viewpoint of kneading temperature and liquid crystal transition temperature, at least one selected from the group consisting of type I liquid crystal polymers and type II liquid crystal polymers is preferred, and type II liquid crystal polymers are more preferred.

[0155] The melting point of the liquid crystal polymer is preferably 280° C. or higher, more preferably 310° C. or higher, and is preferably 380° C. or lower, more preferably 350° C. or lower.

[0156] As the polyetherimide, for example, a polyetherimide having an imide bond and an ether bond in the molecule can be used.

[0157] The glass transition temperature of the polyetherimide is preferably 180° C. or higher, more preferably 200° C. or higher, and is preferably 300° C. or lower, more preferably 280° C. or lower.

[0158] As polyphenylene sulfide, for example, a resin having a structural unit represented by the following formula can be used: The ratio of the structural unit is preferably 70 mol% or more.

[0159] -(Ph-S)-

[0160] Ph in the formula is a phenylene group, and examples of the phenylene group include p-phenylene, m-phenylene, o-phenylene, alkyl-substituted phenylene, phenyl-substituted phenylene, halogen-substituted phenylene, amino-substituted phenylene, amide-substituted phenylene, p,p'-diphenylene sulfone, p,p'-biphenylene, and p,p'-biphenylene ether. Among them, p-phenylene is preferred.

[0161] The melting point of polyphenylene sulfide is preferably 240° C. or higher, more preferably 270° C. or higher, and is preferably 380° C. or lower, more preferably 350° C. or lower.

[0162] Examples of the polyaryletherketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), etc. Among them, PEEK is preferred.

[0163] The melting point of the polyaryletherketone is preferably 320°C or higher, more preferably 340°C or higher, and is preferably 400°C or lower, more preferably 380°C or lower.

[0164] The polysulfone (polysulfone) is not particularly limited, and general polysulfones can be used.

[0165] The glass transition temperature of polysulfone is preferably 180°C or higher, more preferably 200°C or higher, and further preferably 220°C or higher, and is preferably 300°C or lower, more preferably 280°C or lower, and further preferably 260°C or lower.

[0166] The polyethersulfone (polyethersulfone) is not particularly limited, and general polyethersulfone can be used.

[0167] The glass transition temperature of polyethersulfone is preferably 180°C or higher, more preferably 200°C or higher, and further preferably 220°C or higher, and is preferably 300°C or lower, more preferably 280°C or lower, and further preferably 260°C or lower.

[0168] The melting points of liquid crystal polymers, polyetherimides, polyphenylene sulfide and polyaryletherketones are temperatures corresponding to the maximum values ​​in the heat of solution curves when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter (DSC).

[0169] The glass transition temperature of polyetherimide, polysulfone and polyethersulfone can be obtained as follows: a DSC curve is obtained by heating 10 mg of a sample at 10°C / min using a differential scanning calorimeter (DSC822e manufactured by Mettler Toredo), and the glass transition temperature is obtained as the temperature of the midpoint of the two intersections of the extended line of the baseline before and after the secondary transition of the DSC curve and the tangent line at the inflection point of the DSC curve.

[0170] The MFR of the resin B at melting point + 12° C. is preferably 30 g / 10 min or more, preferably 50 g / 10 min or more, more preferably 100 g / 10 min or more, and is preferably 800 g / 10 min or less, more preferably 600 g / 10 min or less.

[0171] The MFR of resin B is a value obtained as the mass (g / 10 minutes) of the polymer flowing out from a nozzle having an inner diameter of 2 mm and a length of 8 mm under a load of 2.16 kg per 10 minutes using a melt indexer (manufactured by Yasuda Seiki Co., Ltd.) in accordance with ASTM D1238.

[0172] In addition, similarly to the above-mentioned liquid crystal polymer, the melting point of the resin B is the temperature corresponding to the maximum value in the heat of fusion curve when the temperature is increased at a rate of 10° C. / min using a differential scanning calorimeter [DSC].

[0173] The thermal decomposition temperature of the resin B is preferably 330° C. or higher, more preferably 350° C. or higher, and is preferably 600° C. or lower, more preferably 550° C. or lower.

[0174] The thermal decomposition temperature of the resin B was measured by the same method as that of the fluororesin A except that the thermal decomposition temperature was measured in air instead of in a nitrogen atmosphere.

[0175] The weight average molecular weight (Mw) of the resin B is preferably 10,000 to 500,000, and the number average molecular weight (Mn) is preferably 5,000 to 20,000.

[0176] The method for measuring Mw and Mn requires selection of a solvent for measurement according to the type of resin B, and the method is GPC as described above.

[0177] The fluororesin A is preferably insoluble in an aprotic solvent.

[0178] In addition, insoluble in an aprotic solvent means that when 10 mL of an aprotic solvent is added to 1 g of a sample at room temperature, the sample is not completely dissolved by visual observation, and the presence of undissolved matter can be confirmed.

[0179] As aprotic solvent, fluorinated aprotic solvent can be exemplified. As fluorinated aprotic solvent, perfluoro aromatic compounds, perfluorotrialkylamines, perfluoroalkanes, hydrofluorocarbons, perfluorocyclic ethers, hydrofluoroethers etc. can be cited. In addition, olefin compounds containing at least one chlorine atom can also be used. Among them, hydrofluoroether (HFE) is preferred.

[0180] Examples of the fluororesin A that is insoluble in an aprotic solvent include FEP, PFA, PTFE, and ETFE.

[0181] Fluororesin A and / or resin B preferably contain amide groups and ester groups. The resin containing amide groups and ester groups is obtained, for example, by reacting an oxazoline compound with a resin containing a carboxyl group. More specifically, amide groups and ester groups are formed by reacting the oxazoline group in the oxazoline compound with the carboxyl group in the resin.

[0182] The presence or absence of an amide group and an ester group can be confirmed by FT-IR measurement.

[0183] In the composition of the present disclosure, the content of the fluororesin A is preferably 10% by volume or more, more preferably 20% by volume or more, and further preferably 30% by volume or more, and is preferably 45% by volume or less, more preferably 40% by volume or less, and further preferably 35% by volume or less.

[0184] In the composition of the present disclosure, the content of resin B is preferably 55% by volume or more, more preferably 60% by volume or more, and further preferably 65% ​​by volume or more, and is preferably 90% by volume or less, more preferably 80% by volume or less, and further preferably 70% by volume or less.

[0185] In the composition of the present disclosure, the total content of the fluororesin A and the resin B is preferably 70% by volume or more, more preferably 80% by volume or more, and even more preferably 90% by volume or more. The upper limit is not particularly limited and may be 100% by volume.

[0186] In the composition of the present disclosure, the volume ratio of fluororesin A to resin B (fluororesin A / resin B) is preferably 10 / 90 or more, more preferably 20 / 80 or more, further preferably 30 / 70 or more, and is preferably 45 / 55 or less, more preferably 40 / 60 or less, further preferably 30 / 70 or less.

[0187] The compositions of the present disclosure may also include additives.

[0188] As the additive, epoxy compounds, amine compounds, oxazoline compounds, acid anhydrides, etc. can be used. Among them, oxazoline compounds are preferred. As the oxazoline compound, the compounds described above can be used.

[0189] Fillers can also be used as additives. Specific examples of fillers include inorganic compounds such as silicon dioxide (more specifically, crystalline silicon dioxide, fused silica, spherical fused silica, etc.), titanium oxide, zirconium oxide, zinc oxide, tin oxide, silicon nitride, silicon carbide, boron nitride, calcium carbonate, calcium silicate, potassium titanate, aluminum nitride, indium oxide, aluminum oxide, antimony oxide, cerium oxide, magnesium oxide, iron oxide, and tin-doped indium oxide (ITO); minerals such as montmorillonite, talc, mica, boehmite, kaolin, montmorillonite, xonotlite, vermiculite, and sericite; carbon compounds such as carbon black, acetylene black, ketjen black, and carbon nanotubes; metal hydroxides such as aluminum hydroxide and magnesium hydroxide; various glasses such as glass beads, glass flakes, and glass hollow spheres; and the like.

[0190] As additives, in addition to the additives described above, general additives for resins such as crosslinking agents, antistatic agents, heat stabilizers, foaming agents, foaming nucleating agents, antioxidants, surfactants, photopolymerization initiators, anti-wear agents, and surface modifiers can also be used.

[0191] Furthermore, resins other than the fluororesin A and the resin B may be used as additives.

[0192] In the composition of the present disclosure, the content of the additive is preferably 0.1% by volume or more, more preferably 1% by volume or more, and further preferably 3% by volume or more, and is preferably 15% by volume or less, more preferably 10% by volume or less, and further preferably 8% by volume or less.

[0193] <Molded article of the present disclosure>

[0194] The shaped body of the present disclosure includes the composition of the present disclosure.

[0195] The molded article of the present disclosure is obtained by molding the composition of the present disclosure. The molding method is not particularly limited, and conventional methods such as injection molding, blow molding, inflation molding, vacuum / air pressure molding, etc. can be used.

[0196] The shaped body of the present disclosure is preferably used as a dielectric material, in particular, a low-dielectric substrate material (eg, an insulating material).

[0197] It should be noted that in this specification, "low dielectric substrate material" refers to a material whose relative dielectric constant at 25°C and 10 GHz is less than 5.0 and whose dielectric loss tangent at 25°C and 10 GHz is less than 0.003, more preferably a material whose relative dielectric constant at 25°C and 10 GHz is less than 4.0 and whose dielectric loss tangent at 25°C and 10 GHz is less than 0.002, and further preferably a material whose relative dielectric constant at 25°C and 10 GHz is less than 3.5 and whose dielectric loss tangent at 25°C and 10 GHz is less than 0.0012.

[0198] When the molded body of the present invention is made into a dielectric material, there is no particular limitation on its use. For example, it can be used for electrical / electronic components such as connectors, sockets, relay parts, coil bobbins, optical pickups, oscillators, printed circuit boards, computer-related parts, etc.; semiconductor manufacturing process-related parts such as IC trays and wafer carriers, VTRs, televisions, irons, air conditioners, stereos, vacuum cleaners, refrigerators, rice cookers, lighting fixtures and other household electrical product parts, lamp reflectors, lamp holders and other lighting fixture parts, CDs, speakers and other audio product parts, optical cable ferrules, telephone parts, fax machine parts, modems and other communication equipment parts, separation claws, heater brackets and other copier-related parts, impellers, fans, gears, gears , bearings, motor parts and casings and other mechanical parts, automobile mechanism parts, engine parts, engine compartment parts, electrical parts, interior parts and other automobile parts, microwave cooking pots, heat-resistant tableware and other cooking utensils, floor materials, wall materials and other insulation, sound insulation materials, beams, columns and other supporting materials, roof materials and other building materials or civil engineering materials, aircraft, spacecraft, space equipment parts, nuclear reactors and other radiation facility parts, marine facility parts, cleaning fixtures, optical equipment parts, valves, pipes, nozzles, filters, membranes, medical equipment parts and medical materials, sensor parts, sanitary equipment, etc.

[0199] <Laminate of the Present Disclosure>

[0200] The laminated body of the present disclosure includes a metal foil and the formed body of the present disclosure.

[0201] As the metal of the metal foil, aluminum, iron, silver, gold, ruthenium, etc. can be cited. In addition, their alloys can also be used. Among them, copper is preferred. As copper, rolled copper, electrolytic copper, etc. can be used.

[0202] The thickness of the laminate of the present disclosure is preferably 10 μm to 1000 μm. In addition, in the laminate of the present disclosure, the thickness of the molded product of the present disclosure is preferably 1 μm to 100 μm.

[0203] The layered product and molded product of the present disclosure are preferably in the form of a sheet having a substantially constant thickness. However, when there are portions with different thicknesses, the thicknesses of 10 portions divided at equal intervals in the longitudinal direction are measured and averaged.

[0204] The laminate of the present disclosure may further include other layers laminated in addition to the above-mentioned metal foil and the molded product of the present disclosure.

[0205] The laminated body disclosed in the present invention is preferably used as a circuit substrate, particularly a printed circuit substrate, a laminated circuit substrate (multilayer substrate), or a high-frequency circuit substrate.

[0206] The high-frequency circuit substrate is a circuit substrate that can also work in a high-frequency band. The high-frequency band can be a band above 1 GHz, preferably a band above 3 GHz, and more preferably a band above 5 GHz. The upper limit is not particularly limited, and can be a band below 100 GHz.

[0207] <Resin of the present disclosure>

[0208] The resin in the present disclosure has a group (I) represented by the following formula, and has a thermal decomposition temperature of 330° C. or higher.

[0209] [Chemistry 6]

[0210]

[0211] (Where R 1 and R 2 The same or different, are hydrogen or organic groups, are not bonded to each other or are bonded to form a ring structure, and the double lines represented by solid and dotted lines are single bonds or double bonds.)

[0212] The resin disclosed in the present invention is a novel resin and has excellent affinity with other resins.

[0213] The resin of the present disclosure preferably has a group (I) at least at a terminal (particularly a terminal of a main chain).

[0214] The resin of the present disclosure may have a branched structure. When the resin of the present disclosure has a branched structure, one of the main chain and the side chain may have the group (I), or both may have the group (I). Preferably, at least the main chain has the group (I).

[0215] The group (I) is the same as the group described in the composition of the present disclosure, and the preferred aspects are also the same.

[0216] The resin of the present disclosure is preferably a thermoplastic resin. Examples of the thermoplastic resin include the same resins as the fluororesin A and the resin B in the composition of the present disclosure.

[0217] The resin disclosed in the present invention may be a crystalline resin or an amorphous resin.

[0218] The resin of the present disclosure is preferably a fluororesin. The fluororesin is the same as the fluororesin A in the composition of the present disclosure, and the preferred aspects are also the same.

[0219] The resin of the present disclosure also preferably has a melt flow rate of 30 g / 10 min or more at the melting point + 12° C. This resin is the same as the resin B in the composition of the present disclosure, and the preferred aspects are also the same.

[0220] The thermal decomposition temperature of the resin disclosed herein may be 330° C. or higher, preferably 350° C. or higher, more preferably 370° C. or higher, and preferably 520° C. or lower, more preferably 500° C. or lower, and further preferably 480° C. or lower.

[0221] It should be noted that when the resin of the present disclosure corresponds to fluororesin A, the thermal decomposition temperature of the resin of the present disclosure is measured by the same method as the thermal decomposition temperature of the above-mentioned fluororesin A, and when the resin of the present disclosure corresponds to resin B, the thermal decomposition temperature of the resin of the present disclosure is measured by the same method as the thermal decomposition temperature of resin B.

[0222] The resin of the present disclosure preferably has at least one of a liquid crystallinity temperature (melting point) and a glass transition temperature of 150° C. or higher.

[0223] The liquid crystalization temperature (melting point) of the resin disclosed herein is preferably 150° C. or higher, more preferably 200° C. or higher, and is preferably 450° C. or lower, more preferably 400° C. or lower, and further preferably 350° C. or lower.

[0224] The glass transition temperature of the resin disclosed herein is preferably 150° C. or higher, more preferably 180° C. or higher, and is preferably 300° C. or lower, more preferably 270° C. or lower, and further preferably 240° C. or lower.

[0225] In addition, the liquid crystal transition temperature (melting point) of the resin of the present disclosure can be measured by the same method as the melting point of the above-mentioned liquid crystal polymer and the like.

[0226] The glass transition temperature of the resin of the present disclosure can be measured by the same method as the glass transition temperature of the above-mentioned polyetherimide and the like.

[0227] The weight average molecular weight (Mw) of the resin disclosed in the present invention is preferably 10,000 to 500,000, and the number average molecular weight (Mn) is preferably 5,000 to 20,000.

[0228] The method for measuring Mw and Mn is the same as above.

[0229] The resins of the present disclosure are preferably insoluble in aprotic solvents.

[0230] The definition of “insoluble in an aprotic solvent” and the types of the aprotic solvent are the same as those described in the composition of the present disclosure.

[0231] When the resin of the present disclosure is a fluororesin that is insoluble in an aprotic solvent, the melt viscosity at 372° C. and a load of 5 kg is preferably 5,000 to 550,000 poise.

[0232] The melt viscosity was calculated from the MFR value of the fluororesin A using a conversion formula (531700 / MFR (g / 10 minutes) = viscosity (poise)).

[0233] The MFR of the fluororesin A was measured by the same method as the MFR of the resin B except that the measurement temperature was 372° C. and the load was 5 kg.

[0234] The resin disclosed in the present invention can be used as a resin modifier, for example, as a resin affinity enhancer, and is particularly suitable as an affinity enhancer for fluororesins and resins having a melt flow rate of 30 g / 10 minutes or more at a melting point of +12°C.

[0235] When the resin of the present disclosure is used as a resin modifier, it is usually mixed with other resins and used as a composition. The amount of the resin modifier of the present disclosure is preferably 1 volume % or more, more preferably 3 volume % or more, and further preferably 5 volume % or more, and preferably 45 volume % or less, more preferably 40 volume % or less, and further preferably 35 volume % or less, in 100 volume % of the mixture with other resins.

[0236] When the resin of the present disclosure is used as a resin modifier, it may be used in combination with other additives. As additives, for example, the substances described in the composition of the present disclosure, such as fillers, may be used.

[0237] The above embodiments are described, but it should be understood that various changes can be made in mode and detail without departing from the spirit and scope of the claims.

[0238] Example

[0239] Next, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited to these examples.

[0240] The materials used in the examples are as follows.

[0241] Fluororesin A

[0242] FEP (TFE unit / HFP unit (molar ratio) = 88.0 / 12.0, melting point: 260°C, solubility in aprotic solvent (HFE): none, amide group and ester group: none)

[0243] PBO modified FEP (thermal decomposition temperature: 430°C, solubility in aprotic solvents (HFE): none, amide and ester groups: yes)

[0244] Pvozo modified FEP (thermal decomposition temperature: 457°C, solubility in aprotic solvents (HFE): none, amide and ester groups: yes)

[0245] PFA (TFE unit / PPVE unit (molar ratio) = 97.2 / 2.8, melting point: 301°C, solubility in aprotic solvent (HFE): none, amide group and ester group: none)

[0246] Pvozo modified PFA (thermal decomposition temperature: 473°C, solubility in aprotic solvents (HFE): none, amide and ester groups: yes)

[0247] (Resin B)

[0248] LCP (Type II liquid crystal polymer, MFR (melting point +12°C): 206.5 g / 10 min, thermal decomposition temperature: 513°C, liquid crystalization temperature (melting point): 313°C, amide group and ester group: None)

[0249] Pvozo modified LCP (Type II liquid crystal polymer, MFR (melting point +12°C): 206.5 g / 10 min, thermal decomposition temperature: 513°C, liquid crystalization temperature (melting point): 313°C, amide group and ester group: yes)

[0250] Production process of PBO modified FEP

[0251] 0.1 g of PBO (1,3-phenylbisoxazoline) and 9.9 g of PGME (propylene glycol monomethyl ether) were added to a 50 cc sample bottle, respectively. After ultrasonic stirring for 10 minutes, 1 g of FEP was added to the sample bottle.

[0252] Next, a stirring bar was placed in the sample bottle, and after reacting in an oil bath at 100° C. for 24 hours, the PGME in the sample bottle was discharged.

[0253] Next, 25 g of methanol was placed in the sample bottle, and the sample bottle was shaken to wash the FEP. Then, the sample bottle was left to stand until the FEP was precipitated, and then the supernatant was discharged. This washing operation was performed 5 times.

[0254] Then, the product remaining in the sample bottle was dried in a dryer at 70° C. for 3 hours, thereby producing a PBO-modified FEP.

[0255] When the obtained PBO modified FEP was measured by FT-IR, the -1 The peaks derived from carbonyl groups were confirmed at 1680-1640 cm -1 A peak of C=N derived from an oxazoline ring and a peak derived from an amide ester were confirmed nearby. From this result, it was confirmed that an oxazoline group existed at the main chain terminal of FEP. The oxazoline group was derived from PBO.

[0256] Production process of Pvozo modified FEP

[0257] 0.1 g of Pvozo (poly-2-vinyl-2-oxazoline, Mw: 110,000, Mn: 47,500) and 9.9 g of PGME (propylene glycol monomethyl ether) were added to a 50 cc sample bottle, and after ultrasonic stirring for 2 hours, 1 g of FEP was added.

[0258] Next, a stirring bar was placed in the sample bottle, and after reacting in an oil bath at 100° C. for 24 hours, the PGME in the sample bottle was discharged.

[0259] Next, 25 g of methanol was placed in the sample bottle, and the sample bottle was shaken to wash the FEP. Then, the sample bottle was left to stand until the FEP was precipitated, and then the supernatant was discharged. This washing operation was performed 5 times.

[0260] Then, the product remaining in the sample bottle was dried in a dryer at 70° C. for 3 hours, thereby preparing Pvozo-modified FEP.

[0261] When the obtained Pvozo modified FEP was measured by FT-IR, the -1 The peaks derived from carbonyl groups were confirmed at 1680-1640 cm -1 A peak of C=N derived from an oxazoline ring and a peak derived from an amide ester were observed nearby. From this result, it was confirmed that an oxazoline group existed at the terminal of the main chain of FEP. The oxazoline group was derived from Pvozo.

[0262] Production process of Pvozo modified PFA

[0263] 0.1 g of Pvozo (poly-2-vinyl-2-oxazoline, Mw: 110,000, Mn: 47,500) and 9.9 g of PGME (propylene glycol monomethyl ether) were added to a 50 cc sample bottle, and after ultrasonic stirring for 2 h, 1 g of PFA was added.

[0264] Next, a stirring bar was placed in the sample bottle, and after reacting in an oil bath at 100° C. for 24 hours, the PGME in the sample bottle was discharged.

[0265] Next, 25 g of methanol was placed in the sample bottle, and the sample bottle was shaken to wash the PFA. The sample bottle was then left to stand until the PFA was precipitated, and the supernatant was discharged. This washing operation was performed 5 times.

[0266] Then, the product remaining in the sample bottle was dried in a dryer at 70° C. for 3 h, thereby preparing Pvozo-modified PFA.

[0267] When the obtained Pvozo-modified PFA was measured by FT-IR, the -1 The peaks derived from carbonyl groups were confirmed at 1680-1640 cm -1A peak of C=N derived from an oxazoline ring and a peak derived from an amide ester were observed nearby. As a result, it was confirmed that an oxazoline group existed at the main chain terminal of PFA. The oxazoline group was derived from Pvozo.

[0268] Production process of Pvozo modified LCP

[0269] 0.1 g of Pvozo (poly-2-vinyl-2-oxazoline, Mw: 110,000, Mn: 47,500) and 9.9 g of PGME (propylene glycol monomethyl ether) were added to a 50 cc sample bottle, and after ultrasonic stirring for 2 h, 1 g of LCP was added.

[0270] Next, a stirring bar was placed in the sample bottle, and after reacting in an oil bath at 100° C. for 24 hours, the PGME in the sample bottle was discharged.

[0271] Next, 25 g of methanol was placed in the sample bottle, and the sample bottle was shaken to wash the LCP. Then, the sample bottle was left to stand until the LCP precipitated, and the supernatant was discharged. This washing operation was performed 5 times.

[0272] Then, the product remaining in the sample bottle was dried in a dryer at 70° C. for 3 h, thereby preparing a Pvozo-modified LCP.

[0273] When the obtained Pvozo modified LCP was measured by FT-IR, the -1 The peaks derived from carbonyl groups were confirmed at 1680-1640 cm -1 A peak of C=N derived from an oxazoline ring and a peak derived from an amide ester were observed nearby. As a result, it was confirmed that an oxazoline group existed at the main chain terminal of LCP. The oxazoline group was derived from Pvozo.

[0274] Examples and Comparative Examples

[0275] Using a circulating twin-screw extruder (Xplore MC15HT, manufactured by Xplore Instruments), 13.72 g of resin B (LCP) and 9.03 g of fluororesin A (FEP) were mixed under the conditions in Table 1. The materials were pre-dry mixed and fed from the feed hopper and mixed at 320°C, 5 minutes, and 500 rpm. After mixing, the sample was collected as a strand.

[0276] The cross section of the obtained strands was observed with a laser microscope to evaluate the morphology after kneading (dispersion state of the resin). It was confirmed that a sea-island structure was formed in which the resin B was the sea and the fluororesin A was the island. However, compared with the comparative example, the dispersed particle size of the island (fluororesin A) in the example was smaller, the dispersion state was good, and the appearance of the strands was also good. In addition, from the results of Example 3, it was confirmed that the Pvozo-modified FEP played an effect as a resin modifier.

[0277] In addition, the evaluation criteria of the strand appearance are as follows.

[0278] A: No roughness or agglomeration is observed on the surface of the strands.

[0279] B: The surface of the wire can be seen to be rough and coagulated.

[0280] [Table 1]

[0281]

Claims

1. A composition comprising a fluororesin A and a resin B having a melt flow rate of 30 g / 10 min or more at a melting point of +12°C, wherein the resin B does not include the fluororesin A. At least one of the fluororesin A and the resin B has a group (I) represented by the following formula, [Chemistry 1] In the formula, R 1 and R 2 The two groups are the same or different, are hydrogen or an organic group, are bonded to each other to form a ring structure or are not bonded to each other, and the double lines represented by solid lines and dashed lines are single bonds or double bonds.

2. The composition according to claim 1, wherein The thermal decomposition temperature of the fluororesin A and / or the resin B is 330° C. or higher.

3. The composition according to claim 1 or 2, wherein The fluororesin A is at least one selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and tetrafluoroethylene / hexafluoropropylene copolymers.

4. The composition according to any one of claims 1 to 3, wherein The resin B is at least one selected from the group consisting of liquid crystal polymer, polyetherimide, polyphenylene sulfide, polyaryletherketone, polysulfone and polyethersulfone.

5. The composition according to any one of claims 1 to 4, wherein The content of the fluororesin A is 10 volume % or more.

6. The composition according to any one of claims 1 to 5, wherein The group (I) is an oxazoline group.

7. The composition according to claim 6, wherein The oxazoline group is derived from an oxazoline compound. 8 . A molded product comprising the composition according to claim 1 .

9. The molded body according to claim 8, which is used for a dielectric material. 10 . A laminate comprising a metal foil and the formed body according to claim 8 or 9 .

11. The laminate according to claim 10, wherein The metal foil is copper.

12. A resin having a group (I) represented by the following formula, and having a thermal decomposition temperature of 330° C. or higher, [Chemistry 2] In the formula, R 1 and R 2 The two groups are the same or different, are hydrogen or an organic group, are bonded to each other to form a ring structure or are not bonded to each other, and the double lines represented by solid lines and dashed lines are single bonds or double bonds.

13. The resin according to claim 12, wherein The resin contains amide and ester groups.

14. The resin according to claim 12 or 13, wherein The group (I) is an oxazoline group.

15. The resin according to claim 14, wherein The oxazoline group is derived from an oxazoline compound.

16. The resin according to any one of claims 12 to 15, wherein The melt flow rate at melting point + 12° C. is 30 g / 10 minutes or more.

17. The resin according to claim 16, wherein The resin is liquid crystal polymer, polyetherimide, polyphenylene sulfide, polyaryletherketone, polysulfone or polyethersulfone.

18. The resin according to any one of claims 12 to 15, wherein The resin is a fluororesin.

19. The resin according to claim 18, wherein The fluororesin is at least one selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers, and tetrafluoroethylene / hexafluoropropylene copolymers.

20. The resin according to claim 18 or 19, wherein The fluororesin is insoluble in an aprotic solvent.

21. The resin according to claim 20, wherein The aprotic solvent is at least one selected from the group consisting of perfluoroaromatic compounds, perfluorotrialkylamines, perfluoroalkanes, hydrofluorocarbons, perfluorocyclic ethers, hydrofluoroethers, and olefin compounds containing at least one chlorine atom.

22. The resin according to any one of claims 12 to 21, wherein The resin is a resin modifier.

Citation Information

Patent Citations

  • Fluoropolymer composition

    JP2001187833A

  • Resin composition and molded article

    JP2018177931A

  • Resin composition for printed circuit boards and production method

    JP2019065061A